Management of esophageal strictures after endoscopic resection for early neoplasia. (January 2021) - Abou Ali, Einas; Belle, Arthur; Hallit, Rachel; Terris, Benoit; Beuvon, Frédéric; Leconte, Mahaut; Dohan, Anthony; Leblanc, Sarah; Dermine, Solène; Palmieri, Lola-Jade; Coriat, Romain; Chaussade, Stanislas; et al.
Background: Endoscopic resection of extensive esophageal neoplastic lesions is associated with a high rate of esophageal stricture. Most studies have focused on the risk factors for post-endoscopic esophageal stricture, but data on the therapeutic management of these strictures are scarce. Our aim is to describe the management of esophageal strictures following endoscopic resection for early esophageal neoplasia. Methods: We included all patients with an endoscopic resection for early esophageal neoplasia followed by endoscopic dilatation at a tertiary referral center. We recorded the demographic, endoscopic, and histological characteristics, and the outcomes of the treatment of the strictures. Results: Between January 2010 and December 2019, we performed 166 endoscopic mucosal resections and 261 endoscopic submucosal dissections for early esophageal neoplasia, and 34 (8.0%) patients developed an esophageal stricture requiring endoscopic treatment. The indication for endoscopic resection was Barrett's neoplasia in 15/34 (44.1%) cases and squamous cell neoplasia (SCN) in 19/34 (55.9%) cases. The median [(interquartile range) (IQR)] number of endoscopic dilatations was 2.5 (2.0–4.0). Nine of 34 (26.5%) patients required only one dilatation, and 22/34 (65%) had complete dysphagia relief following three endoscopic treatment sessions. The median number of dilatations was significantly higher for SCN [3.0 (2–7); range 1–17; p  = 0.02], and in the case of circumferential resection [4.0 (3.0–7.0); p  = 0.03]. Endoscopic dilatation allowed a sustained dysphagia relief in 33/34 (97.0%) patients after a mean follow-up of 25.3 ± 22 months. Conclusion: Refractory post-endoscopic esophageal stricture is a rare event. After a median of 2.5 endoscopic dilatations, 97.0% of patients were permanently relieved of dysphagia. Circumferential endoscopic esophageal resections should be considered when indicated.